The Influence of Live Streaming Quality, Streamer Credibility, and Perceived Enjoyment on Purchase Intention in Live Commerce - Siti Maemunah; Tukkot Hamonangan Immanuel; Imam Jayanto; Dian Parwati (Malaqbi Publisher, 2026)
The rapid growth of live commerce has transformed online shopping by integrating real-time interaction, entertainment, and digital marketing strategies. This study aims to examine the influence of live streaming quality, streamer credibility, and perceived enjoyment on consumer purchase intention in live commerce. A quantitative research approach was employed using a survey method, with data collected from 250 respondents who have experience engaging in live streaming commerce. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that all three variables significantly and positively influence purchase intention. Among them, perceived enjoyment has the strongest effect, followed by streamer credibility and live streaming quality. These findings highlight that emotional and experiential factors play a more dominant role compared to purely technical aspects in influencing consumer behavior. Live streaming quality serves as a foundational factor that enhances clarity and reduces uncertainty, while streamer credibility builds trust and persuasion. Meanwhile, perceived enjoyment drives engagement and encourages purchasing decisions through an entertaining and immersive experience. This study contributes to the literature by integrating technological and psychological factors into a unified model and provides practical implications for businesses to optimize their live commerce strategies by focusing on entertainment value, credible streamers, and high-quality streaming performance.